Uganda Wildlife Society Policy Dialogues 2012 - Namirimu, Teddy; Buyinza, Joel; Nyadoi, Priscilla (Uganda Wildlife Society, 2012)
This Policy Brief has been prepared with the financial assistance of IUCN NL, Wetlands International and Both ENDS, partners in the Ecosystem Alliance. The views expressed, the information and material presented and the geographical and geopolitical designations used in this Policy Brief do not imply the expression of any opinion whatsoever on the part of IUCN NL, Wetlands International or Both ENDS or the institutions and organizations providing these three organizations with funds.